1998
DOI: 10.1046/j.1432-1327.1998.2520036.x
|View full text |Cite
|
Sign up to set email alerts
|

A detailed analysis of the C5a anaphylatoxin effector domain : selection of C5a phage libraries on differentiated U937 cells

Abstract: We have used a phage-display-based system to investigate the effect of simultaneous substitutions within the C5a effector domain. Two different libraries were constructed. In library I, known binding positions 67, 68, 72 and 74 of human complement C5a (hC5a) and in library II, positions 69Ϫ73 of hC5a without C-terminal Arg74 (des-Arg74-C5a) were randomly mutated. In more than 80% (position 72) or 90% (positions 68 and 74) of all cases, the original residues of hC5a were selected from library I, demonstrating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Deletion mutation analysis suggests that both the N- and C-terminal residues are involved in receptor binding and activation. 48 Our studies have suggested that there are several discontinuous regions of C5a that interact with C5aR. 10 Further, studies have shown that C-terminal synthetic peptides as short as eight aa are able to interact and induce C5aR-mediated function, albeit at much higher concentrations of the peptide than the intact C5a molecule.…”
Section: C5a Receptorsmentioning
confidence: 79%
See 1 more Smart Citation
“…Deletion mutation analysis suggests that both the N- and C-terminal residues are involved in receptor binding and activation. 48 Our studies have suggested that there are several discontinuous regions of C5a that interact with C5aR. 10 Further, studies have shown that C-terminal synthetic peptides as short as eight aa are able to interact and induce C5aR-mediated function, albeit at much higher concentrations of the peptide than the intact C5a molecule.…”
Section: C5a Receptorsmentioning
confidence: 79%
“…10 Further, studies have shown that C-terminal synthetic peptides as short as eight aa are able to interact and induce C5aR-mediated function, albeit at much higher concentrations of the peptide than the intact C5a molecule. 48 …”
Section: C5a Receptorsmentioning
confidence: 99%
“…Two portions of 2.5 l each were electroporated into Escherichia coli TG1 cells (Stratagene) using a Bio-Rad pulser set at 25 microfarads, 2.5 kV, and 200 ⍀. Immediately after the pulse, 1 ml of freshly prepared SOC medium (0.5% yeast extract, 2% Tryptone, 10 mM NaCl, 2.5 mM KCl, 10 mM MgCl 2 , 20 mM MgSO 4 , 20 mM glucose) was added, and the cells were grown for 1 h at 37°C and plated on TYE plates (15 g/liter Bacto agar, 10 g/liter Tryptone, 10 g/liter yeast extract, 5 g/liter NaCl) supplemented with 100 g/ml ampicillin and 1% glucose (TYEϩampϩgluc) as described (26). To score the total number of independent transformants, 100 l of appropriate dilutions were plated onto TYEϩampϩgluc plates.…”
Section: Generation Of C5a Mutants-the C5a Mutants Depicted Inmentioning
confidence: 99%
“…Bacteria were grown overnight with shaking at room temperature. The next day, the periplasmic fraction was prepared by freezing and thawing as described (26). CNBr-activated Sepharose (Amersham Biosciences) was coated with C5a-specific mAb 561 (36) according to the manufacturer's instructions.…”
Section: Generation Of C5a Mutants-the C5a Mutants Depicted Inmentioning
confidence: 99%
See 1 more Smart Citation